Influence of Infection of Cotton by Rotylenchulus Reniformis and Meloidogyne Incognita on the Production of Enzymes Involved in Systemic Acquired Resistance - Aryal, Sudarshan K. (The Society of Nematologists, 2011)
Systemic acquired resistance (SAR), which results in enhanced defense mechanisms in plants, can be elicited by virulent and avirulent strains of pathogens including nematodes. Recent studies of nematode reproduction strongly suggest that Meloidogyne incognita and Rotylenchulus reniformis induce SAR in cotton, but biochemical evidence of SAR was lacking. Our objective was to determine whether infection of cotton by M. incognita and R. reniformis increases the levels of P-peroxidase, G-peroxidase, and catalase enzymes which are involved in induced resistance. A series of greenhouse trials was conducted; each trial included six replications of four treatments applied to one of three cotton genotypes in a randomized complete block design. The four treatments were cotton plants inoculated with i) R. reniformis, ii) M. incognita, iii) BTH (Actigard), and iv) a nontreated control. Experiments were conducted on cotton genotypes DP 0935 B2RF (susceptible to both nematodes), LONREN-1 (resistant to R. reniformis), and M-120 RNR (resistant to M. incognita), and the level of P-peroxidase, G-peroxidase, and catalase activity was measured before and 2, 4, 6, 10, and 14 d after treatment application. In all cotton genotypes, activities of all three enzymes were higher (P ≤ 0.05) in leaves of plants infected with M. incognita and R. reniformis than in the leaves of control plants, except that M. incognita did not increase catalase activity on LONREN-1. Increased enzyme activity was usually apparent 6 d after treatment. This study documents that infection of cotton by M. incognita or R. reniformis increases the activity of the enzymes involved in systemic acquired resistance; thereby providing biochemical evidence to substantiate previous reports of nematode-induced SAR in cotton.